Crystal structure of 3-carbamothioylpyridinium thiocyanate - Bouchareb, Hasna (Acta Crystallogr E Crystallogr Commun, 2015)
In the cation of the title salt, C(6)H(7)N(2)S(+)·SCN(−), the C=S bond is oriented trans with respect to the C—C=N fragment in the pyridine ring. The planes of the aromatic ring and the thioamide fragment of the cation make a dihedral angle of 38.31 (4)°. In the crystal, the components are linked by N—H⋯S and N—H⋯N, hydrogen bonds, forming a two-dimensional network parallel to (10-1).